Validity And Reliability Of Senior High School Students' Performance Assessment In Word Processing Materials On Android-Based Informatics Learning - Dwi Marwati; Muhammad Khafid; Wahyu Lestari (UNIVERSITAS PAKUAN, 2023)
This research is part of the research on the Development of Performance Assessment Instruments for Grade VII Junior High School Students on Word Processing Materials in Android-Based Informatics Learning. The purpose of this study was to reveal the content validity, and the reliability of the content and the reliability of the performance assessment instrument for class VII junior high school students' word processing materials that had previously been compiled. The instrument developed is an observation sheet. Content validity analysis was analyzed using Aiken's V formula. Instrument content reliability was analyzed using Ebel's formula with the help of Two Way Anava analysis through SPSS V.26. The results of this study indicate that (1) the observation sheet in the form of a scoring and self-assessment rubric proved valid with an average coefficient of V Aiken 0, 95; (2) the instrument is also stated to be reliable in terms of content with a value of rxx = 0.703; (3) The test instrument proved to be reliable with a Cronbach's Alpha value = 0.929 for the Cronbach's Alpha value before being standardized and 0.931 for the Cronbach's Alpha value after being standardized for 15 statement items, after being tested on 163 class VII students of SMPN 2 Mejobo Kudus for use on students . Based on the results of this study, the instrument for evaluating the performance of Grade VII junior high school students using word processing is appropriate.